Fe, Ni-codoped W18O49 grown on nickel foam as a bifunctional electrocatalyst for boosted water splitting. Issue 33 (6th August 2021) - Hai, Guojuan; Huang, Jianfeng; Cao, Liyun; Kajiyoshi, Koji; Wang, Long; Feng, Liangliang; Liu, Yijun; Pan, Limin
Abstract : Electrocatalytic materials with different doping forms were designed for efficient water splitting. Abstract : Designing cost-effective bifunctional catalysts with high-performance and durability is of great significance for renewable energy systems. Herein, typical Fe, Ni-codoped W18 O49 /NF was prepared via a simple solvothermal method. The incorporation of Fe ions enhanced the electronic interaction and enlarged the electrochemically active surface area. The increased W 4+ leads to a high proportion of unsaturated WO bonds, thus enhancing the adsorption capacity of water. The valence configuration of nickel (Ni) sites in such dual-cation doping is well adjusted, realizing a high proportion of trivalent Ni ions (Ni 3+ ). Due to the orbital interactions, the Fe 3+ /Ni 3+ ions and OER reaction intermediates exhibit strong orbital overlap. The positions of the valence band and conduction band are well modulated. As a result, the Fe, Ni-codoped W18 O49 /NF shows improved electrocatalytic activity, and achieves a low decomposition voltage of 1.58 V at 10 mA cm −2 and retains long-time stability.